Corruption In Nepal: An Anthropological Inquiry - Subedi, Madhusudan Sharma (Dhaulagiri Journal of Sociology and Anthropology, 2006)
For at least a decade and more obtrusively in recent years, the problem of corruption has been at the center of the political agenda in Nepal. It is recognized as one of the chief causes of Nepal’s underdevelopment. It is very widespread, has different manifestations, and is practiced at all levels of society. The Nepali bureaucracy, politician, and the business sector are most seriously affected by, and inextricably involved in corruption. This is really a great challenge to the campaign of modern Nepal. The businesspersons, the politicians, government officials, so called academicians and even consumers are responsible for this. The intention of this paper is to classify the various forms of corruption in order to operationalize the concept for analytical and practical proposes. First, I will outline the different forms of corruption prevailing in Nepal. Secondly, I will propose some issues to fight against corruption, a broader agenda of democratization. DOI: 10.3126/dsaj.v1i0.283 Dhaulagiri Vol.1 (2005) pp.110-128